11m-6+m-1=

Simple and best practice solution for 11m-6+m-1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11m-6+m-1= equation:


Simplifying
11m + -6 + m + -1 = 0

Reorder the terms:
-6 + -1 + 11m + m = 0

Combine like terms: -6 + -1 = -7
-7 + 11m + m = 0

Combine like terms: 11m + m = 12m
-7 + 12m = 0

Solving
-7 + 12m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 12m = 0 + 7

Combine like terms: -7 + 7 = 0
0 + 12m = 0 + 7
12m = 0 + 7

Combine like terms: 0 + 7 = 7
12m = 7

Divide each side by '12'.
m = 0.5833333333

Simplifying
m = 0.5833333333

See similar equations:

| 4x-5(x+3)=6(x+3) | | 10n+2+9-4n= | | 6y-y-7= | | 11d-6d+6= | | -5(x+4)=-2-5x | | x*6-10=-26 | | 1.5x+1.5x(x+8)= | | 3/8q=-1/2 | | 9-7r=-3 | | 4.95=-log(x) | | 16x-2y=6 | | 8+10z=-13 | | 7=t-5.5 | | -4w-6=13 | | d=-16t^2-2t+673 | | -7=-r+1 | | 8x+6=166 | | 65=1.3x | | 7-5c=3c+35 | | 43=-n+8(n+8) | | 9a=0.36 | | 18y=126 | | 9(1+10k)+=17 | | -4-8(7+x)-4x= | | 3.9r=98 | | X+23=-4x-2 | | 21930/35870 | | -2x^2+12x=16 | | -4x-2=x+12 | | x-6+(x-2)=0 | | 7x+3=12x-7 | | x^4-9x^2+9=0 |

Equations solver categories